Group Guidance Service Design in Managing Student Emotions at SMP Negeri 1 Batang Anai - Aulia, Dheva (Lembaga Riset Mutiara Akbar, 2022)
Design of Group Guidance Services in Managing Students' Emotions at SMP Negeri 1 Batang Anai, Thesis, Guidance and Counseling Study Program, Faculty of Social Sciences and Humanities, PGRI University, West Sumatra, Padang, 2022. The background of this research is that there are students who have unstable emotions and cannot control their anger towards the surrounding environment. The purpose of this study is to 1) describe the problem of managing students' emotions 2) make a group guidance service design This research is quantitative descriptive. The population of this study were all students of class VII SMP Negeri 1 Batang Anai totaling 256 students. The sampling technique used the Proportional Random Sampling technique as many as 72 students. The instrument used is a questionnaire, data analysis using the percentage technique. The results of this study reveal that the problem of managing the emotions of students in SMP Negeri 1 Batang Anai is in the very low category. 2) The design of group guidance services in managing students' emotions by providing group guidance services using discussion techniques with the topic of managing emotions. Recommendations to BK teachers to be able to carry out the group guidance service, in order to increase the ability to manage students' emotions